THE RESPONSIBILITY OF TAXPAYERS WHO INTENTIONALLY USE VAT PAYABLE FOR THE OPERATIONAL ACTIVITIES OF A LEGAL ENTITY: (Study of Decision Number 12/Pid.Sus/2022/PN TTE) - Syafrina Aliyah Rachman; Tanudjaja (DE RECHT (Journal of Police and Law Enforcement), 2024)
This study examines the responsibility of taxpayers who intentionally use the payable Value Added Tax (VAT) for the operational activities of a legal entity, within the context of the case Putusan Nomor 12/Pid.Sus/2022/PN Tte. The case focuses on Yan Quedarusman, the commissioner of CV. Samalita Perdana Mitra, who was charged with failing to report and remit collected taxes, resulting in a loss to state revenue amounting to Rp. 716,823,816.00. The defendant used his personal account for transactions, claiming that the company's account was inactive. This study analyzes whether the defendant's actions are in accordance with Indonesian tax regulations, particularly the Tax Law and the 1945 Constitution of the Republic of Indonesia. This research highlights the importance of the legal responsibility principle in relation to tax obligations, as well as the impact of non-compliance with timely and accurate tax reporting. The findings indicate that the defendant's actions were not in accordance with the applicable tax regulations, and emphasize the importance of compliance with tax obligations to prevent losses to the state.